Entrepreneurship: A microenterprise perspective - Moid U. Ahmad (Abhigyan, 2015)
Small businesses and microenterprises enable an individual to earn some livelihood, create value and not create pressure on the available employment avenues. They are a parameter and a measure for social and economic development. They are also good examples of sound economics at micro level. In India we have a plethora of such microenterprises which are a source of earnings, mostly for the poor and uneducated. They also contribute to the economy as a whole by initiating the movement of money, if even at a very small scale. A study of these microenterprises provides an opportunity to derive some business lessons which can be generalized for other entrepreneurs and business. The survey attempts to find interrelationship amongst 30 variables of microenterprises and tries to interpret issues relevant to social development, economic development and poverty alleviation. Such an analysis also provides lessons which can be used to increase the efficiency of management decisions for entrepreneurs and managers. Thus, it becomes imperative to understand the business processes of such small organizations. The findings of the report would be useful for corporate and the policymakers apart from giving inputs to researchers